Relation of Empathy and Leadership Styles of Cadets at USMA - Powers, Jeremiah. (Tufts University. Tisch Library., 2019)
Are leaders born or made? Contemporary developmental science has evolved from a reductionist approach to a dynamic systems approach that recognizes the scientific value of integrating multiple perspectives about leadership development. Assessments of leadership style during a development period in a specific context can provide insight into how leaders are being developed. This research sought to study the relation between leadership and empathy in United States Military Academy cadets during their first two year at the Academy. Cadets completed three separate self-report surveys assessing: (1) their empathy level, using nine items adapted from the Interpersonal Reactivity Index (IRI); and (2) their preferred style of leadership using the Charismatic, Ideological, and Pragmatic (CIP) leadership style measure. Analysis involved using empathy scale scores associated with cadets' first arrival at USMA and CIP scale mean scores for each subscale at three data collection points. Empathy and CIP leadership scores were examined through computing Pearson-product moment correlations, and hierarchical linear regression was used to examine if empathy predicted CIP leadership and if this relation varied by gender. Results showed that empathy accounted for the most variance in a charismatic leadership style. Variation in how gender and empathy interacted with the leadership was found at each time point. Expanding on this research will provide important information on how to best support leadership development of cadets at USMA.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Child Development.; Advisor: Richard Lerner.; Committee: Diane Ryan, and Michael Matthews.; Keyword: Developmental psychology.